SISTEM PUSAT DATA PT. AKSARA SOLOPOS SURAKARTA - Teguh Saudi; Astri Charolina (Universitas Sahid Surakarta, 2014)
Data center information systems is used as a database system PT. Aksara Solopos Surakarta, the core of this system is the maintenance operation news and data access.Over time, based on observations of the authors found several deficiencies, that is: news the upload process takes a long time because of election news for and have to repeat the same number of clicks on each upload news and searching the lack of facilities. Data center information systems PT. Aksara Solopos Surakarta this is used as a data storage news which was published and processed every day. On the system admincan do maintenace news, maintenace account, maintenace category, maintenace channels, searching and downloads. While visitors can only access the news only. Based on the test results by using the method webqual and direct interview of the user obtained the value 89,7% that the quality of the data center's information systems is influenced by the usability and based on interviews with admin data center information systems PT. Aksara Solopos Surakarta that the system that has beendeveloped is now better compared to the previous system primarily on process uploading, searching and there are download button.